Plan estratégico para el supermercado Dicavi cía. ltda., de la ciudad de Zamora, cantón Zamora, provincia de Zamora Chinchipe, para el periodo 2017-2021 - Astudillo Villavicencio, Natalia Carolina (2017)
The present research work proposes a strategic plan for the Dicavi Cía Supermarket. Ltda., Which is dedicated exclusively to commercial production. For the development of this work, we used methods such as inductive to obtain general propositions, deductive to solve the problem, historical analytic to know the background of the Supermarket; Likewise, the use of investigative techniques such as the interview to the manager of the Supermarket and the survey of the 12 workers for the collection of data and information were used. In the Results section, after the evaluation of the external factors of the company, the EFI Internal Factor Assessment matrix was considered, which resulted in a weighted score of 2.80, which means that it maintains a considerable predominance of strengths as it is Good communication between manager and worker and good working climate on the weaknesses which the most outstanding is lack of training to the workers. In addition, in this same section, it was indispensable to carry out the evaluation of internal factors of the Dicavi Cía Supermarket. Ltda., Through the matrix of Evaluation of External Factors EFE, whose weighted result was 2.60, with which it is interpreted that the Supermarket is responding in an excellent way to the opportunities such as quality control and technical standards established by INEN And the active interest rate that favors loans with 9.89% to SMEs against the threats, among which the most outstanding is new ventures dedicated to the same economic activity. Next, the SWOT matrix was established based on the analysis of internal and external factors. Once organized, the High Impact Matrix was built, which allowed us to establish four strategic objectives as the main objectives for a greater growth of the Supermarket: 1) Designing the Business Philosophy. 2) Design a training plan for staff. 3) Design the function manual. 4) Create customer loyalty. 5) Increase business productivity. With the establishment of the strategic objectives, it was possible to formulate or propose the Strategic Plan of the Dicavi Cía Supermarket. Ltda. These strategic objectives are designed to encourage the activities of the company along with its budget that amounts to the amount of $ 4,660.00 dollars; Which is designed to be done within four years. Finally, it presents the conclusions and recommendations in which it is determined that the supermarket will improve its development and positioning in the local market, capturing and improving in the number of customers by at least 50%, as well as solve the problems To the company taking advantage of the opportunities that the market offers to grow and to be strengthened.